Analysis Political Law About Omnibus Law In Indonesia - Ismidar Ismidar; Tamaulina Br. Sembiring; Zakaria Tambunan (Wiraraja University, 2024)
Omnibus Law is a combination of several laws into one regulation, the government's aim in creating an omnibus law is to combine... 1,244 articles and 79 laws in one regulation. One of the laws that are included in the omnibus law is the Manpower Law, in the Draft Omnibus Law on Job Creation it will create 11 changes including Simplification of Licensing, Investment Requirements, Foreign Workers, Working Hours, Worker Rights and Protection, adding types of layoffs, and Strengthening Social Security, so that a fundamental discussion is needed on the Urgency of labor law as a legal rule included in the omnibus law agenda. The purpose of this study is to analyze the Urgency of labor law as a legal rule included in the omnibus law agenda with the problem approach method used by normative legal researchers with a legislative approach and a conceptual approach by examining the laws and regulations regarding the legal politics of the formation of the omnibus law in Indonesia.